2011
DOI: 10.1093/ntr/ntq235
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers of Potential Harm Among Adult Smokers and Nonsmokers in the Total Exposure Study

Abstract: These results contribute to the understanding of the relationship between tobacco smoking and potential biological effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
68
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(83 citation statements)
references
References 36 publications
13
68
2
Order By: Relevance
“…Several studies have shown the inverse association between smoking and bilirubin levels [6,7,17,18]. In our studies, there were more never smokers in the high-TBIL and high-IBIL groups than the low-TBIL and low-IBIL groups, respectively.…”
Section: Discussionsupporting
confidence: 54%
“…Several studies have shown the inverse association between smoking and bilirubin levels [6,7,17,18]. In our studies, there were more never smokers in the high-TBIL and high-IBIL groups than the low-TBIL and low-IBIL groups, respectively.…”
Section: Discussionsupporting
confidence: 54%
“…Biomarkers of tobacco exposure or potential harm have previously been analyzed for cigarette smokers (16)(17)(18)(19)(20)(21)(22), but less information is available about biomarkers associated with cigar consumption. It has been shown that cigar smoke contains significantly higher concentrations of toxic and carcinogenic constituents such as tobaccospecific N-nitrosamines (TSNA), carbon monoxide, and benzene than does cigarette smoke (6).…”
Section: Introductionmentioning
confidence: 99%
“…ACHA survey data collected biannually in the Fall of 2008 through the Spring of 2012 show that 28.5-36.2% of male students reported ever using hookah tobacco compared to 22.6-30.1% of female students (7,(40)(41)(42)(43)(44)(45)(46). Although males have a higher prevalence of hookah tobacco smoking than females, females experience a faster decline in pulmonary function (26,30,47), a greater likelihood for nicotine dependence, and a higher prevalence of respiratory symptoms and lung disease (48).…”
Section: Demographic Characteristicsmentioning
confidence: 99%
“…Similar to other tobacco products, hookah tobacco confers an increased risk for impairment of pulmonary function (26,27), lung diseases (28,29), periodontal disease (28,30), and cardiovascular disease (8). However, hookah tobacco produces higher levels of toxicants than cigarettes (31).…”
Section: Introductionmentioning
confidence: 99%